Hamstring strains in typical training tasks and in isokinetic eccentric contractions of different velocities - McGuigan, M. P.; James, D.; MacDonald, B. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Acute hamstring injuries remain the most prevalent muscle injuries in sport. Muscle strain injuries occur due to high active strain of the muscle (1). The circumstances which have the potential to produce this high active strain in the hamstrings in sprinting have been well documented (2). During late swing, when the hip is flexed, the hamstrings act to decelerate the shank. This results in lengthening of the muscle-tendon unit and therefore potentially reduced capacity for active force generation within the muscle fascicles. The precise timing of muscle injury is not yet clear, but it can be argued that if the lengthening of the muscle fascicles has been excessive then they are not able to generate sufficient force to resist the external force due to body weight when the foot contacts the ground, resulting in further lengthening of the muscle and damage. What has not yet been investigated in vivo is the way in which the active and passive elements of the hamstring muscles behave during eccentric contractions. In order to more fully understand the risk factors for hamstring injuries and the inciting event for injury it is imperative to understand the relative lengthening of the different elements of the muscle. Extensive study of the ankle plantarflexor muscles has revealed that the strain of muscle fascicles does not mimic that of the whole muscle-tendon unit: with the majority of the increase in length required for ankle dorsiflexion in running occurring in the compliant Achilles tendon, and the muscle fascicles shortening slowly (4). In this presentation I explore whether the same de-coupling of muscle fascicle and muscletendon unit occurs in the hamstring muscles. Due to their much longer muscle fascicles one might hypothesise that the strain of their muscle-tendon units is more driven by the length change of the fascicles than the tendon, but conversely the force generating capacity of the active component of the muscle should be sufficient to resist the force due to the inertia of the shank in late swing, and allow the required muscle-tendon unit lengthening to occur in the passive elements. We have used a combination of ultrasound, motion analysis and EMG to determine biceps femoris fascicle length and muscle-tendon unit length during isokinetic eccentric contractions at different velocities and some typical training tasks in order to explore the muscle`s behaviour during controlled eccentric tasks.